Evaluating M&As from a regional perspective: media discourses on the asymmetric internationalization of Vienna's banking sector. Issue 10 (3rd October 2022) - Musil, Robert; Seethaler, Josef
ABSTRACT: Firms are important regional identity anchors. Accordingly, acquisitions by foreign companies are publicly discussed regarding the gains or losses in regional prestige that they bring about. However, the perception and evaluation of mergers and acquisitions (M&As) in public discourse has so far only been marginally analysed. The study therefore examines the interpretation and evaluation of inward and outward M&As in Vienna between 1999 and 2016 by highly reputed local print media providing comprehensive business coverage. The three main approaches are differentiated according to their valuing of the regional impact of M&As – an orthodox, a heterodox, and a relational perspective. These perspectives are operationalized in terms of the concept of 'framing', which refers to the aspects of an issue that are emphasized in media coverage to elicit a certain interpretation and thus, to make the issue socially relevant. The results show a regionally 'uneven' media reception, which is expressed in the application of different frames to inward and outward M&As. Over time, and particularly during the crisis since 2009, the heterodox frame seems to have dominated media evaluation. Hence, the arguments on inward and outward M&As still differ: the implications for the own region seem to influence media evaluations of M&As.